Extracellular and Intracellular Factors in Brain Cancer - Kanwore, Kouminin; Kambey, Piniel Alphayo; Guo, Xiao-Xiao; Abiola, Ayanlaja Abdulrahman; Xia, Ying; Gao, Dianshuai (Frontiers in Cell and Developmental Biology, 2021)
The external and internal factors of the cell are critical to glioma initiation. Several factors and molecules have been reported to be implicated in the initiation and progression of brain cancer. However, the exact sequence of events responsible for glioma initiation is still unknown. Existing reports indicate that glioma stem cells are the cell of glioma origin. During cell division, chromosome breakage, DNA alteration increases the chance of the cell genome modifications and oncogene overexpression. Although the high risk of gene alteration and oncogene overexpression, not everyone develops cancer. During embryogenesis, the same oncogenes that promote cancers have also been reported to be highly expressed, but this high expression does not lead to carcinogenesis raises questions about the role of oncogenes in carcinogenesis. The resistance of cancer cells to drugs, apoptosis, and immune cells does not rely solely on oncogene overexpression, but the defect in the cell organelles machinery (mitochondria, endoplasmic reticulum, and cytoskeleton). This review discusses factors contributing to cancer, we report the dysfunction of the cell organelles and their contribution to carcinogenesis, while oncogene overexpression promotes tumorigenesis, maintenance and progression through the cell adhesion. All of these factors together represent a fundamental requirement for cancer and its development.